Changing land use due to development interventions in the Sibunag watershed - De la Cruz, Juneline S. (1998.)
This study attemps to determine whether present development programs or projects in the Sibunag Watershed affect exixting land uses.
Special Problem - (Cert. in Envrionmental Resource Management) - U. P. in the Visayas.
Keywords: Sibunag watershed